IDENTIFIKASI SENYAWA AKTIF EKSTRAK DAUN JARAK KEPYAR (Ricinus communis) DENGAN ANALISIS FITOKIMIA DAN GC-MS SEBAGAI KANDIDAT SENYAWA OBAT - Sulwiyatul K Sani; Baiq Erna; Atri Sri Ulandari (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2023)
As a tropical country with biodiversity, Indonesia is rich with flora especially those with potential as medicinal plants such as Jarak Kepyar (Ricinus communis). Leaves of jarak kepyar (Ricinus communis) are used as a medicine for wounds, rash, abscess, and fever. Therefore, the purpose of this study was to determine the active compound in ethanol and n-hexane extract of jarak kepyar (Ricinus communis) leaves using phytochemical analysis and GC-MS. The research method used is the experimental method in the laboratory. The steps of the research were extraction of jarak kepyar (Ricinus communis) leaves using 96% ethanol and n-hexane with the maceration method. Furthermore, jarak kepyar (Ricinus communis) leaves extract was analyzed qualitative and quantitatively by phytochemical screening and GC-MS analysis. The results of the phytochemical screening showed that the chemical compounds contained in the ethanol extract of jarak kepyar (Ricinus communis) leaves were flavonoids, alkaloids, terpenoids, tannins and phenolics. While the chemical compounds contained in the n-hexane extract of jarak kepyar (Ricinus communis) leaves are alkaloids. GC-MS analysis of the ethanol and n-hexane extracts of jarak kepyar (Ricinus communis) leaves showed that several compounds that are found in the extract of jarak kepyar (Ricinus communis) leaves such as 2-ethoxycarbonyl-5-oxo-pyrolidine, delta-octalactone, trimethyl ester or trimethyl citrate, quinic acid, 2,3- Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one and methyl oleate have potential as medicinal compounds.